Forensic chemistry and toxicology an essential tool in effective criminal justice system - Cañete, Arlyn M. Dascil (Wiseman's Book Trading, Inc., 2014)
"This book seeks to humbly serve as a guide for Criminology students, reviewees-examinees, law practitioners, Forensic scientists, crime investigators and other law enforcers"--Foreword